Addition of Firik improves the antioxidant and quality characteristics of steamed rice cake (Sulgidduk): Effect of firik on steamed rice cake (Sulgidduk) - Kim, Si Yeon; O, Hyeon bin; Lee, Phyrim; Kim, Young-Soon (Progress in Nutrition, 2019)
Firik (or Frekeh) is a green wheat with high antioxidant activity and dietary fibers. Our aim was to analyze the antioxidant activities, quality characteristics, retarding retrogradation effect and sensory properties of Sulgidduk then to suggest the optimum proportion of firik in Sulgidduk. Five different samples were prepared with different amounts of firik powder (0%, 5%, 10%, 15%, and 20%). Firik has higher water holding capacity than rice: 401.50% and 221.74% respectively. The swelling power was varied with the temperature. Antioxidant activities of Sulgidduk significantly increased (p<0.05). The L-value and a-value significantly decreased, whereas b-value and ∆E increased with the increase in the amount of firik powder (p<0.05). Hardness, cohesiveness, springiness, chewiness, and gumminess decreased but not in a gradual manner (p<0.05). Retrogradation retardation revealed the strongest effect for the group treated with 5-10% firik powder that showed the lowest Avrami exponent. The group treated with 5% powder had the highest score in sensory evaluation test. These results suggest that the addition of 5% firik powder is suitable for improving the consumer acceptability and functionality of Sulgidduk.